Conditional-relatives in Senufo (Gur) and Manding (Mande): The encoding of generalizing relative clauses in West African languages - Dombrowsky-Hahn, Klaudia (AAeO - Afrikanistik-Aegyptologie-Online, 2020)
Different West African languages of the Gur and Mande families have a type of relative clauses additionally marked as conditionals. They function as generalizing relatives and occur often in proverbs. The paper proposes an analysis of these constructions in the Senufo languages Syer ((or Western Karaboro, Burkina Faso) and Supyire (Mali) and in the Manding variety Bambara (Mali). It discusses for each language first the formal aspects of the most typical relative clauses modifying a definite referent, then those of hypothetical and course of events conditionals. This aims at showing the cumulative marking of both the relative and the conditional in the third type, the conditional-relative clauses. In the last section I give an account of the generalizing function of the conditional-relatives arguing that the cumulation of formal means reflects the cumulation of functions. Thus, the encoding of an event in a conditional clause marks it as hypothetical, removing from it any property characteristic of a concrete instance of the event type. This abstraction from a concrete instance is most evident in course of event conditionals, which show a factual ‘whenever’ relationship between the event in the conditional clause and that in the main clause. A relative clause has the function to modify and restrict clausally the referent of a type of entity. The generalizing function of a conditional-relative clause is brought about by the fact that the restricting event is hypothetical and hence abstracted from a real event.